Recovery of copper (II) absorbed in biomass of Cladosporium cladosporioides - Juliana Ribeiro do Carmo; Carlos José Pimenta; Júlia Ferreira da Silva; Sara Maria Chaulfoun de Souza (Scientia Agricola, 2013)
The biosorption process, characterized by the use of biomass for removing metals from aqueous solutions, is an attractive technology using inactive and dead biomasses to remove heavy metals from aqueous solutions in the absence of metabolic activity necessary for intracellular accumulation. The desorption process, which concentrates the metal previously absorbed for possible reuse, is also important. The desorption of copper (Cu) (II) associated with the biomass of Cladosporium cladosporioides (Fres) de Vries was evaluated following the biosorption process (adsorption). Specifically, four eluents were used (all at a concentration 0.1 mol L-1), sulfuric acid, hydrochloric acid, ethylenediaminetetraacetate disodium and calcium chloride, as well as the recovery of Cu (II) desorbed as copper sulfate. After 120 h, 97 % of Cu in solution had been adsorbed. C. cladosporioides can efficiently adsorb Cu (II). Further, 0.1 mol L-1 sulfuric acid was viable and the most efficient for the desorption of the absorbed metal, while ensuring viability of C. cladosporioides after desorption, which is important for the reuse of the biomass in cycles of sorption-desorption.